The impact of pitch counts and days of rest on performance among Major-League baseball pitchers - Bradbury, J. C.; Forman, S. L. (The Journal of Strength and Conditioning Research, 2012)
Although the belief that overuse can harm pitchers is widespread, there exists little evidence to show that the number of pitches thrown and the days of rest affect future performance and injury among adults. The purpose of this study is to quantify the effects of pitches thrown and the days of rest on pitcher performance. We examined performances of major-league baseball starting pitchers from 1988 to 2009 using fractional polynomial multiple regression to estimate the immediate and cumulative impact of pitches thrown and the days of rest on performance, while controlling for other factors that likely affect pitcher effectiveness. Estimates indicate each pitch thrown in the preceding game increased earned run average (ERA) by 0.007 in the following game. Each pitch averaged in the preceding 5 and 10 games increased the ERA by 0.014 and 0.022, respectively. Older pitchers were more sensitive to cumulative pitching loads than younger pitchers were, but they were less affected by pitches thrown in the preceding game. Rest days were weakly associated with performance. In summary, we found that there is a negative relationship between past pitches thrown and future performance that is virtually linear. The impact of the cumulative pitching load is larger than the impact of a single game. Rest days do not appear to have a large impact on performance. This study supports the popular notion that high pitching loads can dampen future performance; however, because the effect is small, pitch-count benchmarks have limited use for maintaining performance and possibly preventing injury.